State control in the aftermath of petroleum policy and governance reform in Mexico: capable of fulfilling constitutional objectives?. (16th March 2019) - Marmolejo-Cervantes, Miguel; Soliman Hunter, Tina
Abstract: When extracting petroleum, a constitutional goal for the Mexican state is to optimize income for the state and to contribute to the long-term development of Mexico. In order to achieve this, Mexico has undergone extreme institutional and legal reforms, opening up fields for private participants, encouraging investment and reforming the governance framework. This article analyses the post-reform changes in light of Nelson's criteria of state intervention, concluding that while Mexico has shifted from an autocratic form of participatory intervention to a form akin to that of Norway, there are further reforms necessary in order for the development of Mexico's petroleum resources to achieve the goals of optimizing income and contributing to the long-term development of the Mexico. Such reforms include legislative reform of the Hydrocarbons Law 2014 to include mandatory field optimization, akin to section 4-1 of the Norwegian Petroleum Activities Act, and a legal requirement for development to aid the Mexican industrial sector and stimulate industrial and economic development, which will significantly contribute to the long-term development of the Mexican nation. Furthermore, the article concludes that although the current Mexican governance framework is capable of delivering the goals of optimization of revenue and long-term development of Mexico, the success will depend on political stability, consensus and a reduction in corruption, which present major challenges to Mexico.